The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1080/00986280802529350
|View full text |Cite
|
Sign up to set email alerts
|

Psychology is a Science: At Least Some Students Think So

Abstract: s (2007) curricular guidelines recommend that students develop both an understanding of how psychologists do research and an appreciation for why scientific thinking is necessary. We surveyed a large sample of psychology majors on specific interests, as well as individual difference variables relevant to scientific thinking. Our results suggest that over time, students' knowledge of scientific thinking increased, whereas their tendency to see psychology as a science did not. Further, students reported greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
62
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 13 publications
13
62
2
2
Order By: Relevance
“…Possible scale scores range from 21 to 105, with higher scores representing higher interest in practitioner activities. Previous research indicates the scale has good internal reliability (α = .88 to .94; Holmes & Beins, 2009;Leong & Zachar, 1991), with comparable findings found in this study (α=.90).…”
Section: Practitioner Orientationsupporting
confidence: 81%
“…Possible scale scores range from 21 to 105, with higher scores representing higher interest in practitioner activities. Previous research indicates the scale has good internal reliability (α = .88 to .94; Holmes & Beins, 2009;Leong & Zachar, 1991), with comparable findings found in this study (α=.90).…”
Section: Practitioner Orientationsupporting
confidence: 81%
“…We recognise that the absolute level of knowledge acquired is low, but this is not unexpected given the short explanation and single example of the topic. The current findings are consistent with previous studies that found students' attitudes were divorced from learning (e.g., Holmes & Beins, 2009;Sizemore & Lewandowski, 2009). They stand in contrast to previous research showing that attitudes toward statistics are related to performance (e.g., Budé et al, 2007;Cashin & Elmore, 2005).…”
Section: Discussioncontrasting
confidence: 55%
“…Students express significant preferences for 'human interest courses' (e.g., psychopathology or personality) and even 'scientific psychology' courses (e.g., physiological or cognitive psychology) over courses in research methods or statistics (Rajecki, Appleby, Williams, Johnson, & Jeschke, 2005). This preference may stem from a student's view of the vocational activities of psychologists, his or her motivation for taking psychology courses (Gallucci, 1997), the student's personality (Holmes & Beins, 2009;Zachar & Leong, 1992), or some combination of these.…”
Section: Introductionmentioning
confidence: 99%
“…A marginally significant negative association was observed between the inherent predictability of human behavior subscale of the Psych-SEBS and psychology misconceptions, and this subscale was also positively associated with self-1 Initial psychometric evaluation of the PAS indicated that this scale may have an underlying three-factor structure with significant conceptual overlap to the Psych-SEBS (see Friedrich, 1996). To our knowledge, however, the factor structure of the PAS has not been confirmed through additional psychometric evaluation, and the vast majority of research subsequent to the initial psychometric evaluation of this scale has utilized overall composite scores instead of subscale scores (e.g., Herstein Gervasio, Wendorf, & Yoder, 2010;Holmes & Beins, 2009). Accordingly, we chose to use composite PAS scores for all analyses in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that EBs specific to the manner in which psychological knowledge is acquired (e.g., through scientific methods) may impact how students approach and perform in their psychology courses. However, more recent research examining associations between scores on the PAS and other seemingly constructrelevant variables has yielded mixed results (e.g., Holmes & Beins, 2009;Lyddy & Hughes, 2011;Provost, Martin, Peacock, Lipp, Bath, & Hannan, 2011), thus throwing into question the criterion-related validity of the PAS and obfuscating the association between psychology-specific EBs and student outcomes. Additional empirical research is thus necessary to clarify the nature of the relationship between psychology-specific EBs and academic functioning.…”
Section: Initial Validation Of An Instrument Measuring Psychology-spementioning
confidence: 99%